Of Donor Coordination, Free-Riding, Darlings, and Orphans: The Dependence of Bilateral Aid on Other Bilateral Giving - Ronald B. Davies; Stephan Klasen (Center for Economic Studies and ifo Institute (CESifo), 2013)
Using data from 1988 to 2007, we examine to what extent bilateral aid flows of an individual donor to a country depend on aid flows from all other bilateral and multilateral donors to that country. We thereby want to assess to what extent donor coordination, free-riding, selectivity, specialization, and common donor motivations drive bilateral aid allocation as these determinants would point to different dependence structures. Using approaches from spatial econometrics and controlling for endogeneity, we find that other bilateral flows lead to a significant increase in aid flows from a particular donor. The effects are particularly pronounced for recipients in Africa and the Middle East and so-called donor orphans who seem to be collectively shunned by bilateral aid donors. The positive dependence also seems be related to donors following the lead of the largest donors. Over time, the positive dependence has become smaller. Overall the results suggest that donor coordination and free-riding are quantitatively less important than common donor interests and selectivity.
Keywords: F35; F42; 330; aid; donor coordination; aid darlings; aid orphans